2012
DOI: 10.2136/sssaj2012.0117n
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Tortuosity and Infiltration Constants in the Beerkan Method

Abstract: It has recently been proposed to couple the Beerkan method with the Beerkan \ud Estimation of Soil Transfer parameters (BEST) algorithm to facilitate the estima-\ud tion of soil hydraulic parameters from an infiltration experiment. Although this \ud simplified field procedure is relatively rapid and inexpensive, it has been doubt -\ud ed if the Beerkan method can represent a valid and reliable alternative to other \ud conventional methods. This study explored the impact of the tortuosity param-\ud eter (p) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…2013 (Figure 1a). The hydrodynamic characteristics of sand and bimodal mixture were estimated through water infiltration experiments using the BEST method developed by Lassabatere et al (2006), which had already been validated analytically and experimentally (Lassabatere et al, 2009;Nasta et al, 2012). The estimated water retention and hydraulic conductivity curves ( Figure 1b) match previous studies on the hydraulic characterization of the glaciofluvial deposits of East Lyon (Lassabatere et al, 2010;Goutaland et al, 2013).…”
Section: Methodssupporting
confidence: 64%
“…2013 (Figure 1a). The hydrodynamic characteristics of sand and bimodal mixture were estimated through water infiltration experiments using the BEST method developed by Lassabatere et al (2006), which had already been validated analytically and experimentally (Lassabatere et al, 2009;Nasta et al, 2012). The estimated water retention and hydraulic conductivity curves ( Figure 1b) match previous studies on the hydraulic characterization of the glaciofluvial deposits of East Lyon (Lassabatere et al, 2010;Goutaland et al, 2013).…”
Section: Methodssupporting
confidence: 64%
“…Additional developments can be thought, including the choice of the constants of the infiltration model, because Nasta et al . () suggested that a proper choice of these constants should be expected to improve the soil hydraulic parameters estimated with BEST. However, estimation procedures of the constants as a function of soil type have still to be developed.…”
Section: Resultsmentioning
confidence: 99%
“…Lassabatère et al (2006) proposed the Beerkan Estimation of Soil Transfer parameters (BEST) procedure to estimate the soil water retention and hydraulic conductivity curves. Because of its simplicity and the physical soundness of the employed relationships and procedures, BEST is receiving increasing attention by the scientific community to tackle specific problems (Mubarak et al, 2009a(Mubarak et al, ,b, 2010Gonzalez-Sosa et al, 2010;Lassabatère et al, 2010;Yilmaz et al, 2010;Bagarello et al, 2011) and to test and possibly improve or simplify specific experimental and analytical procedures (Minasny and McBratney, 2007;Bagarello et al, 2009Bagarello et al, , 2011Bagarello et al, , 2014cYilmaz et al, 2010;Nasta et al, 2012;Xu et al, 2012). However, only a few comparisons of the predicted soil properties with data collected by other experimental methods can still be found in the literature (Yilmaz et al, 2010;Aiello et al, 2014;Bagarello et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Beerkan infiltration data were interpreted using the "BEST" algorithm (Lassabatere et al, 2006), which derives the entire set of hydraulic parameters through fitting infiltration data on the analytical infiltration model proposed by Haverkamp et al (1994). This model has been recently validated on generated numerical data (Lassabatere et al, 2009) and field data including coarse materials (Di Prima et al, 2016;Lassabatere et al, 2010;Nasta et al, 2012;Yilmaz et al, 2013Yilmaz et al, , 2010. The mean saturated hydraulic conductivity was 3.5.10 -5 m/s.…”
Section: Modeling: Flow Equations and Soil Hydraulic Propertiesmentioning
confidence: 99%